Role of exosomal competitive endogenous RNA (ceRNA) in diagnosis and treatment of malignant tumors. Issue 5 (2nd May 2022) - Mao, Mingwen; Zhang, Jingyu; Xiang, Yizhen; Gong, Mengdan; Deng, Yongqin; Ye, Dong
ABSTRACT: Malignant tumors are a threat to human health, thus it is critical to better understand the mechanism of tumor occurrence and development and to find key therapeutic targets. Competitive endogenous RNA (ceRNA) is a type of RNA molecule that includes mRNA of coding-protein, pseudogenes, long non-coding RNA (lncRNA), and circular RNA (circRNA) etc. It is created through a competitive combination of common small RNA (miRNA) and has an inhibitory effect on mRNA translation. ceRNA regulate the post transcriptional expression of genes by competitively binding to common microRNAs (miRNAs).Studies have shown that cernas are involved in tumor cell proliferation, invasion and migration, drug resistance, angiogenesis, as well as tumor immunity, and so on, affecting the progression of tumor development. This article reviews the reported roles of exosomal ceRNA in the diagnosis and treatment of malignant tumors and the mechanisms underlying these. Graphical abstract: uf0001